An update on HIV-testing at a London sexually transmitted diseases clinic: long-term impact of the AIDS media campaigns. Issue 3 (June 1990) - Beck, E J; Donegan, C; Kenny, C; Cohen, C S; Moss, V; Terry, P; Underhill, G S; Jeffries, D J; Pinching, A J; Miller, D L
Abstract : Trends in the number of tests for HIV-1 antibody at a London sexually transmitted diseases clinic showed substantial changes between September 1985 and June 1988. From an average of 100 tests per month between September 1985 and August 1986, the average increased to 365 tests per month for September 1986 to August 1987. This levelled off at 243 tests per month between September 1987 and June 1988. The average number of positive tests per month between September 1985 and June 1988 remained constant, though the number of seropositive tests in females increased. Male and female populations displayed similar temporal patterns. The greatest increase was seen in the tests generated by heterosexual males and females with no other risk factors. This group generated 42% of the 8012 tests performed during the study period. The Clinic's catchment area predominantly included London and surrounding areas and temporal patterns were similar for residents from each of the Thames Regions. The temporal patterns observed coincided with periods of increased media attention on HIV infection/AIDS and involved campaigns by the popular press, television, Department of Health Education Authority. The increase in tests during the time of maximum media exposure, the subsequent plateau at a level substantially higher compared with the period preceding the media campaigns and the large increase in heterosexual males and females tested, all suggest that the campaigns have contributed to increasing awareness of HIV infection/AIDS as a major contemporary public health problem.